Processo de destoxificação da torta da semente de Jatropha curcas L. (pinhão-manso) utilizando enzimas extracelulares de macrofungos - Cunha, Joice Raísa Barbosa (2017)
The oleaginous plant Jatropha curcas is a highly promising species for producing biodiesel oil, however, a toxicity of co-products (seed cake or bran) makes its cultivation and industrialization process less profitable. These co-products, seed cake and bran, have highly nutritious composition containing formulations of feed formulations for monogastric or ruminant animals, provided they are suitably detoxified and validated. Phorbol esthers are the main toxic substances present in Jatropha curcas seeds cake(JCSC). The detoxification by phorbol esthers degradation may be by physical, chemical, biological or even combined processes. Thus, this work aimed at a detoxification of JCSCby means of extracellular enzymes obtained from macrofungal culture by submerged fermentation (FSM) and solid state fermentation (FES). The degradation results using the enzymatic extracts (EBE) of the FSM and FES by the macrofungs were different. The EBE-FSM of F17 and the EBE-FES of F3 and F10 were able to reduce the phorbol esters to non-toxic levels, i.e. 0.09 mg of phorbol ester per gram of cake. F17's EBEFSM was the only one capable of degrading 100% of phorbol esthers. Some enzymatic activities were determined with crude extracts. Lipase and esterase activity were not detected. F17 EBE-FSM showed 583.99 U / mL, 64.09 U / mL, 43.64 U / mL, 0.144 U / mL for laccase, total peroxidases, protease, and manganese peroxidase, respectively. Another FSM EBE fungus was highlighted for F2, with degradation of 88% of phorbol esthers. The extract of this fungus showed high protease activity (336.67 U / mL) and activities of laccase, total peroxidases and manganese peroxidase of 101.89 U / mL, 25.57 U / mL and 0.05 U / mL, respectively. The results point to the enzymatic treatment of JCSCas a promising alternative for phorbol esther detoxification, and a detoxifying activity of macrofungus may be associated with an increase in laccase activity.